MEMBANGUN IMAJINASI ANAK SD MELALUI PEMBELAJARAN SENI RUPA BERBASIS TEORI BELAJAR KONSTRUKTIVISME DAN HUMANISME (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of constructivism and humanism learning theories in building elementary students’ imagination through art education. The problem addressed in this study is that art learning in elementary schools is often teacher-centered and limits students’ opportunities to explore their imagination and creativity. This research employs a qualitative approach using a literature review method by examining relevant books, scientific journals, and previous research findings. The results show that constructivism supports the development of imagination through active learning, exploration, and experience-based creative processes. Meanwhile, humanism emphasizes the importance of self-expression, emotional development, and personal freedom, which significantly contribute to students’ imaginative growth. The integration of these two theories creates a student-centered learning environment that encourages creativity, engagement, and meaningful learning experiences. Therefore, the implementation of constructivism and humanism is highly relevant in enhancing students’ imagination and improving the quality of art education in elementary schools.